The Effect of Perceived Quality, Price, and Product Safety on Loyalty Consumer XYZ Products - Kharisma Husna Wirasti; Mochammad Maksum; Muhammad Prasetya Kurniawan; Anggoro Cahyo Sukartiko (Agroindustrial Journal, 2020)
Herbal skincare products are becoming more popular nowadays as consumers’ concern regarding the negative side effects of synthetic ingredients are rising as well. XYZ is a newcomer herbal skincare brand from Indonesia and currently has not become one of the 10 famous cosmetic brands in Indonesia. This research was conducted to determine the description of consumer perceptions regarding the quality, price and safety of XYZ products and its influence on consumer loyalty. Questionnaires are distributed online by using google forms to make it easier to cover a wide area. Data collection is done by nonprobability sampling method using purposive and snowball sampling. There were 400 respondents obtained with the criteria of women who have bought and used XYZ products in Indonesia. This research used quantitative, qualitative and descriptive analysis methods. The obtained data was then analyzed by using multiple linear regression method with the help of SPSS software. Based on the conducted research, the results showed the average consumer agrees that XYZ has good product quality, affordable prices and safe to use. Perceived quality, price and safety have a significant effect on the XYZ consumer loyalty products, both partially and simultaneously. Quality perception has the strongest influence whereas, safety perception has the weakest influence on the consumer loyalty.